Relevansi Tempat Prakerin, Pengalaman Bermakna Saat Praktikum dan Iklim Kelas Terhadap Kematangan Vokasional Siswa SMK di Kota Blitar - Putro, Maulana Nur Antoro; Prasetya, Didik Dwi; Chisbiyah, Lismi Animatul (BRILIANT: Jurnal Riset dan Konseptual, 2024)
The aim of this research is to reveal the relationship between the place of internship (X1), meaningful experiences during the practicum (X2), and classroom climate (X3) on vocational maturity (Y) both partially and simultaneously and to describe each variable. The research design used is quantitative with descriptive correlational research. The sample from this research was class Based on data analysis, it is known that there is a significant relationship between the relevance of the internship site and vocational maturity at 26%, while the relationship between meaningful experiences during practicum and vocational maturity is 17% and the relationship between class climate and vocational maturity is 55%. Thus, the effective contribution of the independent variable (X) to the dependent variable (Y) is 98%. The conclusion of this research is that there is a positive and significant relationship, both partially and simultaneously, between the relevance of the internship site, meaningful experiences during practicum and classroom climate on the vocational maturity of class XII vocational school students majoring in Electrical Power Installation Engineering in Blitar City.Â